Estimating vehicle ego-motion and piecewise planar scene structure from optical flow in a continuous framework - Neufeld, Andreas; Berger, Johannes Peter; Becker, Florian; Lenzen, Frank; Schnörr, Christoph (Pattern Recognition, 2015)
We propose a variational approach for estimating egomotion and structure of a static scene from a pair of images recorded by a single moving camera. In our approach the scene structure is described by a set of 3D planar surfaces, which are linked to a SLIC superpixel decomposition of the image domain. The continuously parametrized planes are determined along with the extrinsic camera parameters by jointly minimizing a non-convex smooth objective function, that comprises a data term based on the pre-calculated optical flow between the input images and suitable priors on the scene variables. Our experiments demonstrate that our approach estimates egomotion and scene structure with a high quality, that reaches the accuracy of state-of-the-art stereo methods, but relies on a single sensor that is more cost-efficient for autonomous systems.
Gesehen am 07.03.2019